Corporate Net Lending A Review of Recent Trends - André, Christophe (OECD Economics Department Working Papers, 2007)
Since 2001, OECD corporate net lending has risen sharply. This paper examines the main forces at play behind this run-up and provides some insight into whether and how they might possibly unwind in the future, a process that may already be underway. It shows in particular that, the increase is partly temporary with some of it likely to fade with the cycle and the ongoing adjustments in the financial and housing sectors. On the other hand, part of the increase reflects structural changes in corporate behaviour and in their environment and is likely to persist. The paper also points to cross-country differences reflecting, for example, the role of competiveness in Japan and continental Europe, and of the financial sector in the United Kingdom